Variable antennas positions solution to reduce pointing errors due to wind speed and temperature coupled effects during free space optical link using matrix Rician pointing error model - Mbezi, Michel Teuma; Eke, Samuel; Som, Idelette Hermine Judith; Mouangue, Ruben Martin (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
Pointing errors (PE) during free space optical (FSO) transmission can be caused by laser beam wander due to thermal and wind dynamic instability. The aim of this work is to study the coupled effects of temperature and wind speed on PE using matrix Rician pointing error (MRPE) model; then show how variable antennas height can reduce PE due to wind speed and temperature coupled effects. To achieve this purposes, average PE expression was established using MRPE model. Then considering a Gaussian beam wave and Monin–Obukhov similarity functions for the structure parameters of temperature, explicit relationship was established between average PE, temperature and wind speed. It comes out of this study that under dynamic turbulence, one can appropriately modify temperature to reduce PE due to dynamic instability and reciprocally. Depending on turbulence large cells or frozen turbulence eddies distribution, PE can be reduced by appropriately modified antennas height or the distance between transmitter and receiver. That is why this work suggests to install variable or dynamic antennas (rather than fixed ones) which could intelligently modify its positions according to laser beam wander created by atmospheric turbulence.
Optica Applicata, Vol. 53, 2023, nr 3, s. 393-406
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; atmospheric turbulence; pointing errors; free space optical transmission; Rician pointing error model